Pendampingan Penyusunan Pembukuan Koperasi Desa - NURCAHYO DARMAWAN, ARI; YUSWANTO NUGROHO, ARIEF; Ali Tamrin, Muhamad; ADI WIJAYA, YULIAN; HARIS WIJAYAKUSUMA, HAFID; SALIM, AGUS (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2024)